BODY LANGUAGE AND CULTURE: A COMPARATIVE STUDY OF ENGLISH AND UZBEK SOMATIC EXPRESSIONS - Valisher Azamovich Tangriyev (Western European Studies, 2025)
This study addresses somatism-based paralinguistic communication in both Uzbek and English, researching in detail how parts of the body and its motions convey meaning and embody cultural values. Employing comparative analysis, the study compares expression through several types of language structures, including idiomatic, proverb, and gestural forms. In its analysis, both general and specific cultural aspects of nonverbal expression become evident, with head nod and head shaking, for example, being proven to have a level of universality, but with variation in connotations and symbolic values regarding specific parts of the body in each language. In both instances, Uzbek language tends to evoke community values and reverence towards elders, such as clasped hands and "oq fotiha" ritual, and in contrast, English language tends to evoke individuality and mastery over emotion. Overall, these observations present a strong case for awareness of cultures in cross-cultural communication, in that nonverbal cues can have immensely disparate meanings in cultures, and for deeper analysis of language, culture, and nonverbal behavior, opening doors for a new level of effective cross-cultural practice
Keywords: Nonverbal communication; paralinguistics; kinesics; somatisms